Spiral Microchannels with Trapezoidal Cross Section Fabricated by Femtosecond Laser Ablation in Glass for the Inertial Separation of Microparticles - Ala’aldeen Al-Halhouli; Wisam Al-Faqheri; Baider Alhamarneh; Lars Hecht; Andreas Dietzel (Micromachines, 2018)
The fabrication and testing of spiral microchannels with a trapezoidal cross section for the passive separation of microparticles is reported in this article. In contrast to previously reported fabrication methods, the fabrication of trapezoidal spiral channels in glass substrates using a femtosecond laser is reported for the first time in this paper. Femtosecond laser ablation has been proposed as an accurate and fast prototyping method with the ability to create 3D features such as slanted-base channels. Moreover, the fabrication in borosilicate glass substrates can provide high optical transparency, thermal resistance, dimensional stability, and chemical inertness. Post-processing steps of the laser engraved glass substrate are also detailed in this paper including hydrogen fluoride (HF) dipping, chemical cleaning, surface activation, and thermal bonding. Optical 3D images of the fabricated chips confirmed a good fabrication accuracy and acceptable surface roughness. To evaluate the particle separation function of the microfluidic chip, 5 μm, 10 μm, and 15 μm particles were focused and recovered from the two outlets of the spiral channel. In conclusion, the new chemically inert separation chip can be utilized in biological or chemical processes where different sizes of cells or particles must be separated, i.e., red blood cells, circulating tumor cells, and technical particle suspensions.